Currency Fluctuations and Islamic Stock Indices in Emerging Markets - Mubarok, Faizul (JURISMA : Jurnal Riset Bisnis & Manajemen, 2023)
This research aims to explain why Islamic stock indexes tend to track the currency exchange rates of emerging countries. Granger causality is used in this analysis, and it is applied to daily data beginning with the day the index was first formed for each country. The Islamic stock indices of Malaysia, Indonesia, and India were employed as a research sample in this study. According to the findings of the research, there is only a correlation in one direction between the Islamic stock index and the currency exchange rate. Both the Islamic stock indexes in Malaysia and India have an effect on the currency exchange rate in that nation, whereas the currency exchange rate in India affects the Islamic stock index. This finding is helpful as a source of data in determining policies for the development of the Islamic financial system because it was discovered that. Keywords: Islamic Stock; Granger Causality; Exchange Rates; Developing Country